The value of cone beam computed tomography in the detection of salivary stones prior to sialendoscopy. Issue 2 (February 2018) - van der Meij, E.H.; Karagozoglu, K.H.; de Visscher, J.G.A.M.
Abstract: This study aimed to assess the value of cone beam computed tomography (CBCT) in the detection of salivary stones in patients with signs and symptoms of salivary gland obstruction. A total of 142 major salivary glands were analysed in a cohort of 127 patients with signs and symptoms of salivary gland obstruction. CBCT scans were performed in order to determine the presence of one or more salivary stones. All glands were also investigated by sialendoscopy. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were calculated for the submandibular gland, the parotid gland, and the whole group, based on the observers' abilities to diagnose the presence or absence of calculi in the CBCT scan using the sialendoscopy data as the gold standard. Fifty salivary stones were detected in the CBCT scans of the 142 glands analysed: 34 in the submandibular gland and 16 in the parotid gland. The sensitivity (94%), specificity (90%), positive predictive value (84%), and negative predictive value (97%) for the whole group were good to excellent, with an overall accuracy of 92%. CBCT appears to be an ideal first-line imaging modality for patients with signs and symptoms of obstructed major salivary glands.